2020
DOI: 10.35194/agsci.v10i2.1157
|View full text |Cite
|
Sign up to set email alerts
|

RESPON MULTIPLIKASI ANGGREK BULAN (Phalaenopsis sp.) TERHADAP PENAMBAHAN BEBERAPA KONSENTRASI BAP (Benzyl Amino Purine) PADA MEDIA IN VITRO

Abstract: Jenis anggrek yang paling banyak diminati dan dibudidayakan adalah anggrek bulan (Phalaenopsis sp.). Perbanyakan anggrek bulan dapat dilakukan dengan metode alternatif yang lebih efektif yaitu dengan melalui kultur in vitro. Tujuan penelitian adalah mengetahui pengaruh penambahan beberapa konsentrasi BAP (Benzyl Amino Purine) terhadap multiplikasi, waktu muncul tunas (HST), jumlah tunas, waktu muncul daun (MST), dan jumlah daun anggrek bulan (Phalaenopsis sp.). Penelitian dilakukan di Laboratorium Pemuliaan Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The other study about Phalaenopsis sp. was given BAP cytokinins, with the number of shoots having a substantial impact starting at 4 WAP [19]. Another element that may affect it is that at the age of 10 WAP, a large number of potential shoots are there but cannot be counted since their plumula have not yet pierced the soil surface.…”
Section: 1the Effect Of Explant Types Bap and Naa Combinations And Th...mentioning
confidence: 99%
“…The other study about Phalaenopsis sp. was given BAP cytokinins, with the number of shoots having a substantial impact starting at 4 WAP [19]. Another element that may affect it is that at the age of 10 WAP, a large number of potential shoots are there but cannot be counted since their plumula have not yet pierced the soil surface.…”
Section: 1the Effect Of Explant Types Bap and Naa Combinations And Th...mentioning
confidence: 99%
“…Green, pale green, and yellowish-green callus formed SEs whereas yellow and yellowish-green callus turned brown [14]. BAP inhibit chlorophyll degradation and regulate embryonic [37]. BAP is a hormone that can stimulate cell division and induced shoot multiplication [38].…”
Section: Pgrs From Microalgamentioning
confidence: 99%
“…Based on the research results of Syamsiah et al (2020), the addition of BAP with a concentration of 2.00 mg/L was the best treatment with the fastest shoot emergence time of 16.80 DAP (day after planting) and the fastest leaf emergence time of 25.20 DAP and the best number of leaves with an average of 14.4 leaves at the end of the observation, which was a week to 12. Hartati et al (2016), in their research also revealed that the addition of ZPT BAP 3 ppm had a significant effect on the increase in root length and increase in plantlet height, so that increasing the concentration level of BAP could increase the vegetative growth response of orchid explants.…”
Section: Introductionmentioning
confidence: 99%